Political Economy of Solid Minerals Governance in Nasarawa State, Nigeria: A Rentier State Analysis (1999 - 2020) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Nasarawa State is widely described as the “home of solid minerals” because metallic, industrial, and gemstone resources are distributed across its thirteen local government areas. Despite this abundance, the governance of solid minerals in Nigeria places ownership and control under the Federal Government. Anchored in Rentier State Theory, this paper examines the political economy of solid minerals governance in Nasarawa State between 1999 and 2020, focusing on how dependence on external oil rents shapes subnational incentives to exploit local mineral wealth. The study adopted a mixed-method design combining a cross-sectional survey with key-informant interviews, supported by documentary and institutional analysis. The survey covered 400 respondents drawn from thirteen purposively selected mining-affected wards and villages, and from relevant institutions; 376 questionnaires returned were used for analysis while unstructured interviews with selected stakeholders provided additional insight. Documentary evidence from official reports, policy documents, budgets, and published sources was used. The study finds that the state is permitted to participate only as a corporate actor and revenue collector, but not as a regulator, and has largely relied on federation account instead of building a robust solid minerals economy. Evidence attributes the state’s weak interest in solid minerals to its dependence on oil revenue, while existing state-level instruments for mineral revenue collection are perceived as ineffective. The paper concludes that Nasarawa’s status as a subnational rentier state explains the paradox of mineral abundance and underdevelopment and calls for reforms that strengthen state capacity, improve transparency in derivation, and create incentives for solid minerals governance.